Relative pavement performance for dual and wide-based tyre assemblies using a finite element method - Casey, Dermot; Airey, Gordon; Grenfell, James (ASTM International, 2017)
There is a need to assess the realistic tire contact pressure created by a tire in contact with a pavement. The contact pressure is a function of tire type, axle loading, and tire inflation pressure (TiP). The research carried out considered dual tire and wide-based tire assemblies across a range of axle loading and TiP. These contact pressures were incorporated into a finite element package (CAPA-3D) and modelled on a simple pavement structure. The strains from this modelling were sorted to produce key strains associated with the mechanisms of surface distress, near surface distress, deep asphalt distress, and the subgrade. The main distress mechanisms were top down cracking, asphalt cracking/rutting, bottom-up fatigue cracking, and subgrade rutting. This gave a method to fairly compare the dual and wide-based tire assemblies with the same axle loading and TiP. The analysis gave interesting results for the different distress mechanisms of the pavement. The wide-based tire gives consistently higher shear strains for all the areas of distress investigated. There is great variation in surface and near surface shear strains due to the different combinations of axle loading and TiP. It is clear that the wide-based tire is a more damaging tire for all combinations of TiP and axle loading. It is also apparent that how these factors interact has a great influence on the damaging potential of a tire.